Designing an Educational Website regarding Recycling of Plastic Waste into Roads - Eddy Suryanto Soegoto; J. M. Ramana; L. S. Rafif (Universitas Pendidikan Indonesia (UPI), 2021)
Plastic waste is closely related to the environment, which is also related to human life. The impact of waste that we can feel is flooding. Plastic waste is very difficult to decompose naturally; thus, it has not been a serious concern due to the lack of human awareness of the environment. The purpose of this research is to educate the public so that plastic waste can be processed into something useful by recycling it into paving blocks for roads. The research method used was qualitative research methods. This study discusses the design of an educational website about recycling waste into roads. This website aims to educate the public to be more concerned about the environment by utilizing waste by recycling it into roads. This research’s discussion is the design of an educational website about waste recycling for the community and create a community that cares about the environment. The benefit of this research is to create a society that cares about the environment and can process their plastic waste independently.